Sinostoma yunnanicum, the first nemastomatine harvestman in China (Arachnida: Opiliones: Nemastomatidae) - Martens, Jochen (Zootaxa, 2016)
The easternmost Nemastomatinae species, Sinostoma yunnanicum n. gen., n. sp., from northern Yunnan, China is described. It extends the geographic distribution of Nemastomatinae by roughly 3000 km southeastwards. Within Nemastomatinae Sinostoma displays plesiomorphic characters, including the long, basic bulb of the truncus shaft and the extremely short glans of penis, armed with short robust spines. Sinostoma may represent a relict line in the early evolution of nemastomatine harvestmen.